Ammonium and Phosphate Removal from Aqueous Solutions by Zeolite and Gravel: Kinetics and Adsorption Isotherms - Georgios D. Gikas; Paraskevas Parlakidis; Neofytos Chamalis (Applied Sciences, 2025)
Although constructed wetlands (CWs) are a viable solution for wastewater treatment, substrate selection significantly affects their performance. This study evaluated the adsorption behavior of ammonium and orthophosphate on natural zeolite (coarse- and fine-grained) and coarse gravel using kinetic and isotherm experiments. Coarse materials are intended for use as filler media in CWs to address problems such as clogging. Ammonium removal due to adsorption reached 96.20% and 96.49% for coarse and fine zeolite, respectively, and 16.84% for gravel. For orthophosphate, the removal was 11.46% and 12.81% for coarse and fine zeolite, respectively, and 6.70% for gravel. Kinetic analysis showed that the adsorption of both nutrients followed the pseudo-second-order model. Zeolite exhibited high ammonium adsorption capacities (181.87 and 174.23 mg/kg), with granulometry showing minimal effect. The orthophosphate adsorption capacities were lower (11.76 and 12.35 mg/kg for zeolite; 6.44 mg/kg for gravel). Isotherm modeling indicated that ammonium adsorption fitted better to the Langmuir model (monolayer adsorption), while orthophosphate followed the Freundlich model (heterogeneous surface adsorption). Ζeolite adsorbed six times more ammonium and twice as much phosphate as gravel. These findings suggest that natural zeolite is an effective and sustainable CW substrate, enhancing nutrient removal and serving as an economical and environmentally friendly alternative to traditional filler media.